Sustainability of Public Finance During The COVID-19 Outbreaks in Indonesia - Aan Jaelani; Tika Fatichah Hanim (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
AbstractThis paper will describe the sustainability of public finances in the form of government policies in managing the budget for handling COVID-19 in Indonesia. The impact of this pandemic can cause an economic crisis in Indonesia so that the policies to be taken in the financial sector will determine the sustainability of public finance itself. The qualitative method applied in this paper by utilizing secondary data can provide analysis in the management of government finances for economic stimulus. Public finance which is the main source in achieving government goals for the welfare of the community is used to handle COVID-19 in the form of budget allocations to meet health infrastructure and various economic stimuli to ensure community survival, economic resilience in the industrial sector, and prepare for the continuation of current economic activities and after the pandemic ends.Â Keywords: Sustainability, public finance, maqasid shariah, COVID-19, Coronaviruses, economic stimulusAbstrakArtikel ini akan menjelaskan keberlanjutan keuangan publik dalam bentuk kebijakan pemerintah dalam mengelola anggaran untuk penanganan COVID-19 di Indonesia. Dampak pandemi ini dapat menyebabkan krisis ekonomi di Indonesia sehingga kebijakan yang akan diambil di sektor keuangan akan menentukan keberlanjutan keuangan publik itu sendiri. Metode kualitatif yang diterapkan dalam makalah ini dengan memanfaatkan data sekunder dapat memberikan analisis dalam pengelolaan keuangan pemerintah untuk stimulus ekonomi. Keuangan publik yang merupakan sumber utama dalam mencapai tujuan pemerintah untuk kesejahteraan masyarakat digunakan untuk menangani COVID-19 dalam bentuk alokasi anggaran untuk memenuhi infrastruktur kesehatan dan berbagai rangsangan ekonomi untuk memastikan kelangsungan hidup masyarakat, ketahanan ekonomi di sektor industri, dan mempersiapkan kelanjutan kegiatan ekonomi saat ini dan setelah pandemi berakhir.Â Kata kunci: Keberlanjutan, keuangan publik, maqasid syariah, COVID-19, Coronavirus, stimulus ekonomi